In the constitutional restoration: the process of agrarian distribution in Puebla, Mexico (1917-1920) - Martínez Merino, Luis Mauricio (2024)
The purpose of this article is to analyze the institutional implementation of agrarian distribution and its difficulties in Puebla, Mexico, during the Carrancista constitutional period from 1917 to 1920. First, I briefly explain the process of land distribution and its results in the last months of the year 1917. Then, I analyze the intensity of the political-administrative work of agrarian distribution in the state and its main impediments of application between the years 1918 and 1919. Highlighting the importance and work of the local agrarian office to carry out the allocation of land in the state through the written press. After this analysis, I conclude that in the year 1920, although the Puebla Carrancista government attempted the distribution for political and economic purposes, the bureaucratization of the institutional framework, the opposition of property owners and the military, and the disagreement with the distribution obtained by the people themselves, substantially limited its success.